Pengaruh Minat Belajar Siswa Terhadap Hasil Belajar Statistik di SDN Wirun 3 - Wibowo, Bhismo Aji; Restyowati, Eni; Ratnaningsih, Annisa; Murtiyasa, Budi; Setyaningsih, Nining (LP. Ma'arif Janggan Magetan, 2024)
This research aims to investigate the influence of students' interest in learning on statistics learning outcomes at SDN Wirun 3. The research uses a correlational approach to evaluate the relationship between students' interest in learning and statistics learning achievement. Data collection methods include surveys, academic records, and observations to understand students' learning interests. Data analysis uses correlation and regression techniques to assess the strength of the relationship between interest in learning and statistical learning achievement as well as other factors that influence it. The results of this work show a strong positive relationship between students' learning interest and their achievement in statistics courses, with approximately 49.8% of the variation in statistics achievement being explained by the level of learning interest. The data shows a high level of enthusiasm for learning among students, with average scores for interest in learning quite high and academic performance in moderate but strong statistics. The correlation coefficient of 0.706 between interest in learning and academic achievement indicates a significant correlation, underscoring the importance of building interest in learning to improve educational outcomes. These results confirm that increasing interest in learning can be a key strategy to advance students' academic achievement, especially in the subject of statistics.